Los glacis de raña en el «macizo» de Valronquillo (sector noroccidental del Campo de Calatrava, Ciudad Real) - Muñoz Jiménez, Julio; García Rayego, José Luis (Anales de Geografía de la Universidad Complutense, 1986)
Sin resumen